Genome-wide methylation screen in low-grade breast cancer identifies novel epigenetically altered genes as potential biomarkers for tumor diagnosis - Faryna, Marta; Konermann, Carolin; Aulmann, Sebastian; Lorenzo Bermejo, Justo; Diederichs, Sven; Rom, Joachim; Weichenhan, Dieter; Schirmacher, Peter; Sinn, Peter; Gerhäuser, Clarissa (The FASEB journal, 2012)
Aberrant DNA methylation constitutes a well-established epigenetic marker for breast cancer. Changes in methylation early in cancer development may be clinically relevant for cancer detection and prognosis-based therapeutic decisions. In the present study, a combination of methyl-CpG immunoprecipitation (MCIp) and human CpG island (CGI) arrays was applied to compare genome-wide DNA methylation profiles in 10 low-grade in situ and invasive breast cancers against 10 normal breast samples. In total, 214 CGIs were found to be hypermethylated in ≥6 of 10 tumors. Functional term enrichment analyses revealed an overrepresentation of homeobox genes and genes involved in transcription and regulation of transcription. Significant hypermethylation of 11 selected genes in tumor vs. normal tissue was validated in two independent sample sets (45 tumors and 11 controls, 43 tumors and 8 controls) using quantitative EpiTyper technology. In tumors, median methylation levels of BCAN, HOXD1, KCTD8, KLF11, NXPH1, POU4F1, SIM1, and TCF7L1 were ≥30% higher than in normal samples, representing potential biomarkers for tumor diagnosis. Using the 90th percentile of methylation levels in normal tissue as cutoff value, 62-92% of in situ samples (n=13), 72-97% of invasive samples from the first validation set (n=32), and 86-100% of invasive samples from the second validation set (n=43) were classified as hypermethylated. Hypermethylation of KLF11 and SIM1 might also be associated with increased risk of developing metastases. In summary, early methylation changes are frequent in the low-grade pathway of breast cancer and may be useful in the development of differential diagnostic and possibly also prognostic markers.—Faryna, M., Konermann, C., Aulmann, S., Bermejo, J. L., Brugger, M., Diederichs, S., Rom, J., Weichenhan, D., Claus, R., Rehli, M., Schirmacher, P., Sinn, H.-P., Plass, C., Gerhauser, C. Genome-wide methylation screen in low-grade breast cancer identifies novel epigenetically altered genes as potential biomarkers for tumor diagnosis.
Gesehen am 10.10.2018